Empress Dowager Cixi the concubine who launched modern China - Chang, Jung. (New York Alfred A. Knopf, 2013)
In 1852, at age sixteen, Cixi was chosen as one of Emperor Xianfeng?s numerous concubines. When he died in 1861, their five-year-old son succeeded to the throne. Cixi at once launched a coup against her son?s regents and placed herself as the true source of power?governing through a silk screen that separated her from her male officials.
Includes bibliographical references (pages 403-415) and index.
Keywords: Cixi, Empress dowager of China, 1835-1908.